Влияние состава металлических включений в кристаллах синтетического алмаза на их термостойкость - Боримский, А.И.; Нагорный, П.А.; Делеви, В.Г.; Чипенко, Т.Ю.; Крикун, В.Н. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The influence of the ratio between the components of iron-based solvents for carbon of the Fe-Сo, Fe-Ni systems and the amount of carbide-forming additives (chromium or chromium carbide) in the solvents on the thermostability of the resulting crystals has been established. The conception of the formation of the phase composition of the solvents for carbon such as Fe–Co–Cr₃C₂ and Fe–Ni–Cr₃C₂, which offer enhanced thermostability of the diamond crystals, has been suggested.